Environmental Consciousness and Adoption of Green Banking Services - Kandaramath Hariharan, Akhila; Nedumaran , Ganeshan (Mercados y Negocios, 2025)
This article explores the relationship between customer awareness and the adoption of green banking services at the State Bank of India (SBI) in the Malabar region. The outcome reveals the factors influencing the adoption of these services and the associations between customer awareness and the adoption of Green Banking Services (GBS) in SBI. The SBI has implemented various green banking services to reduce the environmental impact. Customer awareness of these green banking practices is significant, with studies indicating that most customers are familiar with such services. However, the adoption rate can vary based on customer age and awareness. In the Malabar region, exploring this relationship would involve assessing how aware customers are of these services and how likely they are to adopt them, potentially influenced by factors such as age, education, and environmental consciousness.